Radiofrequency coils for ultra-high field body MRI - Farhat, Sedig (2013)
In this thesis, the probes were modelled and constructed at the SPMMRC. All measurements were performed on a 7T Philips scanner. The coils have been successfully evaluated. The dipole, loops, strip line and wrist probes for imaging the pelvis, knee and wrist were tested for clinical use at 7T. Two elements wrist coil can pick up signals from the whole region of interest. The advantage is more uniformity of field of view and better sensitivity. The in vivo MRI images acquired in the wrist showed the two elements provided the good quality images for the human wrist. The second study is microstrip line probe. The current flows over the flat-strip were computed, it showed that a significant increase of current close to the edges. This result agrees with theory. We did not use the strip line coil to image a human body, because the coil generated a high SAR/B1 +2 level in the region of interest. The third study was of a coil of two square loops. One way of achieving decoupling is to use the overlapping technique to decouple the coils in the simulation. It produced high signal-to-noise ratio and provides a large field of view. Finally, the dipole has been developed for in vivo MRI applications. We presented a novel model for determining the length of the PECs required for tuning the dipole at 298 MHz. The efficiency, field of view and homogeneity were improved by adding the flat strip, two strips and array strips dipole. The SAR/B1 +2 generated by the dipoles was much less than produced by the loop coil and strip line coil in the pelvis. The dipoles showed the desired improvement in SNR and homogenous coverage. Coverage goes much further into the pelvis and knee as well.